Strategi Pemasaran 7P Restoran Bertema Autentik di Bale Raos sebagai Potensi Wisata Kuliner di Area Keraton Yogyakarta - Sahlit Sugesti Sugesti (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
Indications of successful management of cullinari such as a restaurant is a significant increase in the target number of tourists visiting. Therefore, it is necessary to have the right and targeted marketing strategy. This study aims to analyze and describe the marketing strategy of Bale Raos restaurant The autentic Taste in tourism area Keraton Yogyakarta. Research used qualitative methods. Informants sampled are general manager, marketing, operational manager and visitorAs of Bale Raos restaurant. Data was collected used interviews, observation, and documentation. Based on the research results show the right marketing strategy to increase quality product and service by segmenting targeting and positioning and collaboration of good product, price sale, place, promotion, people, process and physical evidance.